Biodegradable PEG-poly(ω-pentadecalactone-co-p-dioxanone) nanoparticles for enhanced and sustained drug delivery to treat brain tumors - Chen, Evan M.; Quijano, Amanda R.; Seo, Young-Eun; Jackson, Christopher; Josowitz, Alexander D.; Noorbakhsh, Seth; Merlettini, Andrea; Sundaram, Ranjini K.; Focarete, Maria Letizia; Jiang, Zhaozhong; Bindra, Ranjit S.; Saltzman, W. Mark (Biomaterials, 2018)
Intracranial delivery of therapeutic agents is limited by penetration beyond the blood-brain barrier (BBB) and rapid metabolism of the drugs that are delivered. Convection-enhanced delivery (CED) of drug-loaded nanoparticles (NPs) provides for local administration, control of distribution, and sustained drug release. While some investigators have shown that repeated CED procedures are possible, longer periods of sustained release could eliminate the need for repeated infusions, which would enhance safety and translatability of the approach. Here, we demonstrate that nanoparticles formed from poly(ethylene glycol)-poly(ω-pentadecalactone-co-p-dioxanone) block copolymers [PEG-poly(PDL-co-DO)] are highly efficient nanocarriers that provide long-term release: small nanoparticles (less than 100 nm in diameter) continuously released a radiosensitizer (VE822) over a period of several weeks in vitro, provided widespread intracranial drug distribution during CED, and yielded significant drug retention within the brain for over 1 week. One advantage of PEG-poly(PDL-co-DO) nanoparticles is that hydrophobicity can be tuned by adjusting the ratio of hydrophobic PDL to hydrophilic DO monomers, thus making it possible to achieve a wide range of drug release rates and drug distribution profiles. When administered by CED to rats with intracranial RG2 tumors, and combined with a 5-day course of fractionated radiation therapy, VE822-loaded PEG-poly(PDL-co-DO) NPs significantly prolonged survival when compared to free VE822. Thus, PEG-poly(PDL-co-DO) NPs represent a new type of versatile nanocarrier system with potential for sustained intracranial delivery of therapeutic agents to treat brain tumors.